2007
DOI: 10.1111/j.1551-2916.2007.02093.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbothermal Synthesis of α‐SiC Micro‐Ribbons

Abstract: We report the synthesis of microscopic α‐SiC ribbons (belts) on the surface of a graphite rod at 1800°–1900°C by a carbothermal process. The width of the ribbons produced ranged from 500 nm to 5 μm and the aspect ratio was up to 400. The ribbon thickness ranged from 50 to 800 nm. Their growth mechanism was explained by accelerated growth along the twin boundary. SiC whiskers grew on the rod along with the ribbons. Frequently, ribbons were growing from the tip of a whisker or whiskers were growing from the edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…7 Band gap of zincblende nanoparticles were estimated to be around 3 eV from photoluminesence measurements. With a similar carbothermal method, microribbons 8 with widths in the range of 500 nm -5 µm and thickness of 50-500 nm were synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…7 Band gap of zincblende nanoparticles were estimated to be around 3 eV from photoluminesence measurements. With a similar carbothermal method, microribbons 8 with widths in the range of 500 nm -5 µm and thickness of 50-500 nm were synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…1 Owing to its excellent physical and chemical properties, silicon carbide (SiC), a typical wide band gap semiconductor, is a very attractive material for the applications in harsh environment, such as high temperature, high power, and high frequency. 2 In particular, SiC has many polymorphs, such as 3C (2.39 eV), 6H (3.02 eV), 4H (3.26 eV), and 2H (3.33 eV). Among these polytypes, 3C-SiC and 6H-SiC are of great interest because these materials are used for the fabrication of electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…After that, a number of techniques have been developed to synthesize SiC nanowires, including the sol–gel [ 9 ], vapor–liquid–solid [ 10 ], vapor–solid [ 11 ], laser ablation [ 12 ] and chemical vapor deposition (CVD) [ 13 ] methods. More recently, SiC micro-/nanoribbons have been successfully synthesized by several research groups [ 14 - 16 ]. For instance, Xi et al [ 15 ] reported the growth of cubic SiC (3C-SiC) nanobelts via the reaction of tetrachlorosilane, ethanol and lithium powder in an autoclave at low temperature (600°C) and suggested a lithium-assisted mechanism of SiC nanostructure growth.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Xi et al [ 15 ] reported the growth of cubic SiC (3C-SiC) nanobelts via the reaction of tetrachlorosilane, ethanol and lithium powder in an autoclave at low temperature (600°C) and suggested a lithium-assisted mechanism of SiC nanostructure growth. Yushin et al [ 16 ] synthesized α-SiC micro-ribbons by a carbothermal reaction of silicon dioxide and graphite at high temperature (1,800–1,900°C). Wu et al [ 14 ] reported the synthesis of bicrystalline SiC nanobelts via a thermal evaporation and condensation process with silicon powder and multi-wall carbon nanotubes as the raw materials at 1,250°C.…”
Section: Introductionmentioning
confidence: 99%